Pembuatan Sistem Informasi Rekam Medis Bagian Filing di Rumah Sakit Citra Husada Kabupaten Jember - Muzaffatul Hasan; Sustin Farlinda; Feby Erawantini; Andri Permana Wicaksono (Politeknik Negeri Jember, 2020)
TheÂ Filing medical records information system is a computerized information that can also be used to help medical records officers in the filing unit when borrowing and returning medical record files and to help them when doing a retention. Filing information system at Citra Husada Hospital, of Jember Regency is still using a manual system for recording the loan file of medical record and also there is no recording date system for returning medical record file. The purpose of this study was to design and create a medical record information system for the filing section at Citra Husada Hospital, Jember Regency using the waterfall method. Data collection uses interviews, observation and FGD (Focus Group Discussion). In the process of designing this system using a Flowchart System, Context Diagrams, Data Flow Diagrams, Entity Relationship. Digram and in implementing programs using Microsoft Visual Basic 2010. The results of this study are the making of a medical record information system for filing to facilitate officers in controlling medical record documents in filing through borrowing, repayment and retention. The next researcher is expected to be able to integrate with the existing SIMRS so that filling in the medical record data can automatically appear when in the filing section